Histopathological growth patterns modify the prognostic impact of microvascular invasion in non-cirrhotic hepatocellular carcinoma. Issue 4 (April 2022) - Meyer, Yannick M.; Beumer, Berend R.; Höppener, Diederik J.; Nierop, Pieter M.H.; Doukas, Michail; de Wilde, Roeland F.; Sprengers, Dave; Vermeulen, Peter B.; Verhoef, Cornelis; IJzermans, Jan N.M.
Abstract: Background: Microvascular invasion (MVI) is an established prognosticator in hepatocellular carcinoma (HCC). Histopathological growth patterns (HGPs) classify the invasive margin of hepatic tumors, with superior survival observed for the desmoplastic HGP. Our aim was to investigate non-cirrhotic HCC in light of MVI and the HGP. Methods: A retrospective cohort study was performed in resected non-cirrhotic HCC. MVI was assessed prospectively. The HGP was determined retrospectively, blinded, and according to guidelines. Overall and disease-free survival (OS, DFS) were evaluated by Kaplan–Meier and multivariable Cox regression. Results: The HGP was determined in 155 eligible patients, 55 (35%) featured a desmoplastic HGP. MVI was observed in 92 (59%) and was uncorrelated with HGP (64% vs 57%, p = 0.42). On multivariable analysis, non-desmoplastic and MVI-positive were associated with an adjusted HR [95%CI] of 1.61 [0.98–2.65] and 3.22 [1.89–5.51] for OS, and 1.59 [1.05–2.41] and 2.30 [1.52–3.50] for DFS. Effect modification for OS existed between HGP and MVI (p < 0.01). Non-desmoplastic MVI-positive patients had a 5-year OS of 36% (HR: 5.21 [2.68–10.12]), compared to 60% for desmoplastic regardless of MVI (HR: 2.12 [1.08–4.18]), and 86% in non-desmoplastic MVI-negative. Conclusion: HCCs in non-cirrhotic livers display HGPs which may be of prognostic importance, especially when combined with MVI.